FAKTOR DOMINAN YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA DI AKADEMI KEPERAWATAN WILLIAM BOOTH SURABAYA - ., Ethyca Sari, Yuliana Sedin (S1 Keperawatan, 2013)
Learning achievement is the end result in person and used to achieve success during sebaga ikuran enrolled in a school. Based on the observations of the author in Akademi Keperawatan William Booth Surabaya students who receive optimal learning achievement with a cumulative GPA â¥ 3.00 start first semester - VI only achieved by the same students. This is caused by various factors. Factors affecting the achievement of physiological factors, psychological factors, family support factors, environmental factors, school, community environmental factors. The purpose in doing this study is to mengidantifikasi dominant factor affecting student achievement in Akademi Keperawatan William Booth Surabaya. The design of this study